A flame-retardant, heat-insulating aerogel light-shielding coating fabric and its preparation method
By preparing SiO2 aerogel particle coating modified by nucleotide and dopamine condensation product on the light-shielding fabric, the problems of insufficient thermal insulation effect of the light-shielding fabric and the harm of traditional flame retardants are solved, and the efficient flame retardant and thermal insulation performance is improved, and the fabric is maintained.
Patent Information
- Application Number
- CN202310871113.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-17
- Publication Date
- 2025-07-22
- Estimated Expiration
- 2043-07-17
AI Technical Summary
The thermal insulation effect of existing light-shielding fabrics is limited, and traditional flame retardants are harmful to human health and the environment, so environmentally friendly and efficient flame retardant insulation materials are needed.
Modified aerogel particles are prepared by condensing nucleotides with dopamine to form a condensation product and combining them with SiO2 aerogel particles, and a mixed polyacrylate slurry is coated on the surface of the light-shielding fabric to form a flame-retardant and heat-insulated aerogel light-shielding coating.
The high flame retardant and thermal insulation properties of the light-shielding fabric are achieved. The renewal time and smoldering time are less than 2s, the damage length is less than 6cm, and it has excellent water-washing resistance. The thermal insulation temperature difference is large, and the flame retardant performance is not affected by water-washing.
Smart Images

Figure GDA0005425023560000081 
Figure GDA0005425023560000091
Abstract
Description
Technical Field
[0001] The present invention relates to a flame-retardant, heat-insulating aerogel light-shielding coating fabric and a preparation method thereof, belonging to the technical field of functional textile processing. Background Art
[0002] Light-shielding fabrics are widely used in home textiles and outdoors, and are commonly used for curtains, sunshades, etc. In addition to household use, they are also often used in places such as hotels, cinemas, and large shopping malls.
[0003] Light-shielding coating fabrics are processed by coating on the surface of ordinary fabrics. Usually, light-shielding agents such as titanium dioxide, carbon black or other coatings are added to the coating agent. After multiple coating finishes, the light-shielding effect is achieved. When light irradiates the surface coating of the fabric, reflection or absorption occurs, so that the light cannot pass through the fabric. At present, the common coating methods for light-shielding fabrics are foam coating and transfer coating, among which foam coating is the most common. Foam coating is to inject air into the coating paste, and through special treatment by a foaming device, the coating paste is highly foamed into a uniform and delicate foam state, and then it is coated on the textile. After baking and film-forming, it adheres to the fabric surface to complete the coating process of the fabric. Transfer coating is a coating method of transferring a formed continuous film to a fabric substrate, which is an indirect coating process.
[0004] In recent years, researchers have adopted various means to explore the surface coating finishing process of the base fabric in order to improve the heat-insulating effect of light-shielding coating fabrics. The specific methods include: ① adding nano-titanium dioxide to the coating paste to improve the sunshade and heat-insulating effect by enhancing the solar reflectance; ② adding zirconia or aluminum oxide to the coating paste to block the heat generated by irradiation from transferring to the sunshade material substrate side; ③ by increasing the number of coating layers, coating thickness or fabric gram weight, strengthening reflection, radiation or heat barrier to achieve the purpose of insulating and cooling the material. However, at present, the heat-insulating effect of light-shielding coating fabrics prepared by these methods is limited, and there is still a large room for improvement.
[0005] Endowing light-shielding coating fabrics with flame-retardant properties can effectively control the fire risk to the lowest level and increase the chance of escape. Since once the flame spreads to light-shielding fabrics widely used, such as curtains, the burning speed is extremely fast, and the flame can reach the ceiling within only a few minutes. Therefore, people have attached great importance to the flame retardancy of curtains and other light-shielding fabrics. At present, halogen-based and phosphorus-based flame retardants are widely used, but halogen-based flame retardants and some organophosphorus flame retardants pose a threat to human health and even cause cancer. With the increasing attention of consumers to health, ecological environment protection, and the requirements of environmental regulations, the development of eco-friendly flame retardants and their application methods has received more and more attention. It has been found that some bio-based materials in nature have the prospect of being used as flame retardant materials. They have the advantages of biodegradability, non-toxicity, environmental protection, etc. Developing such bio-based eco-friendly flame retardants meets the requirements of the sustainable development of the textile industry.
[0006] 5'-Adenylic acid is a new type of bio-based flame retardant. 5'-Adenylic acid consists of phosphoric acid (acid source), ribose (carbon source), and nitrogenous base (gas source), and its flame retardant mechanism is the synergistic effect of condensed-phase flame retardancy and gas-phase flame retardancy combined. The liquid phosphoric acid in the thermal decomposition products of 5'-adenylic acid flame-retarded textiles covers the textiles, which can effectively prevent heat conduction and thermal radiation. Metaphosphoric acid generated by the dehydration of phosphoric acid under thermal action can further polymerize to form polyphosphoric acid, which can reduce the thermal decomposition and pyrolysis temperature of fiber macromolecules in textiles. After the fibers are quickly dehydrated and carbonized, a carbon residue covering layer is formed on the surface of the textiles, which can play a role in isolating air, reducing the overflow of light flammable gases generated by fiber pyrolysis, and heat conduction. Ribose will also be carbonized under the action of polyphosphoric acid to form a carbon layer, increasing the coating of the carbon layer on the fibers. The nitrogenous base generates non-combustible gases such as NH3 under the action of heat, and these gases play a flame retardant role in two aspects: (1) The overflowing gases can dilute the concentration of oxygen and the flammable gases generated by fiber pyrolysis; (2) The gases locked in the carbon layer increase the intermolecular distance after heating, causing the carbon layer to expand. The expanded carbon layer is separated from the fibers, which can better play the role of heat insulation.
[0007] However, when using 5'-adenylic acid alone for flame retardant processing of textiles, the flame retardant effect is limited, and it is also necessary to cooperate with other flame retardants to achieve better flame retardant performance. Silica aerogel is a nano-lightweight porous material with air as the main component and amorphous SiO2 as the basic skeleton, having a complex three-dimensional network structure. Its basic physical properties are: apparent density 0.003 - 0.35 g / cm3, specific surface area 800 - 1000 m2 / g, porosity 80.0% - 99.8%, average pore size 20 nm, and thermal conductivity 0.008 - 0.043 W / (m·K). It simultaneously encompasses properties such as low thermal conductivity, low density, high porosity, high light transmittance, high specific surface area, low refractive index, and low sound velocity, and has characteristics such as heat insulation, flame retardancy, and high temperature resistance, thus having broad application prospects in many fields. SiO2 aerogel has received the attention of many researchers as a functional filler in coatings. As an important component of the coating, SiO2 aerogel endows the coating with special functions such as heat insulation, flame retardancy, high temperature resistance, and sound insulation and sound absorption. Summary of the Invention
[0008] In view of the above problems, the object of the present invention is to provide a method for preparing a flame-retardant and heat-insulating aerogel light-shielding coating fabric. A condensing agent is used to condense nucleotides and / or nucleosides containing amino groups with dopamine (DOPA), and then the condensation product is adhered to the surface of SiO2 aerogel particles. The coating obtained by mixing the prepared modified aerogel with a polyacrylate slurry is coated on the surface of the light-shielding coating fabric to obtain a light-shielding coating fabric with high flame-retardant and heat-insulating properties at the same time.
[0009] To achieve the above object, the present invention provides a method for preparing a flame-retardant and heat-insulating aerogel light-shielding coating fabric, which specifically includes the following steps:
[0010] (1) Preparation of the condensation product: A condensing agent, a condensation activator, nucleotides and / or nucleosides, and dopamine (DOPA) are added to an acidic solution to obtain a mixed solution, and the mixture is stirred and reacted at 30-40 °C for 1-6 hours. After the reaction, it is freeze-dried to obtain the condensation product;
[0011] (2) Preparation of the modified aerogel particle dispersion: The condensation product obtained in step (1) is added to an alkaline solution, and nano-SiO2 aerogel particles are added thereto to obtain a reaction mixture, which is stirred and reacted at room temperature for 1-6 hours. After the reaction, a modified aerogel particle dispersion is obtained;
[0012] (3) Preparation of the aerogel light-shielding coating fabric: A polyacrylate slurry and a kerosene thickener are added to the modified aerogel particle dispersion obtained in step (2) to prepare a coating finishing solution, which is coated on the surface of the light-shielding fabric and dried to obtain the aerogel light-shielding coating fabric.
[0013] In an embodiment of the present invention, in step (1), the concentration of the condensing agent in the mixed solution is 1-10 g / L, the concentration of the condensation activator is 1-10 g / L, the concentration of the nucleotides and / or nucleosides is 1-10 g / L, and the concentration of the dopamine is 1-10 g / L.
[0014] In an embodiment of the present invention, the condensing agent is 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC), and the condensation activator is N-hydroxysuccinimide (NHS).
[0015] In an embodiment of the present invention, in step (1), the pH of the acidic solution is 4-6.
[0016] In an embodiment of the present invention, in step (1), the acidic solution includes at least one of hydrochloric acid, sulfuric acid, citric acid, acetic acid, and sodium acetate, and the concentration of the acid in the acidic solution is 0.1-0.5 M.
[0017] In one embodiment of the present invention, in step (1), the nucleotide includes at least one of adenylic acid, cytidylic acid, and guanylic acid, and the adenylic acid includes 5'-adenylic acid or nicotinamide adenine dinucleotide.
[0018] In one embodiment of the present invention, in step (1), the nucleoside salt includes at least one of monosodium 5'-adenylic acid, disodium 5'-adenylic acid (AMP-Na2), and monosodium nicotinamide adenine dinucleotide.
[0019] In one embodiment of the present invention, in step (2), in the reaction mixture, the concentration of the condensation product is 1-10 g / L, and the concentration of the nano-SiO2 aerogel particles is 5-50 g / L.
[0020] In one embodiment of the present invention, in step (2), the pH of the alkaline solution is 7-9.
[0021] In one embodiment of the present invention, in step (2), the alkaline solution is at least one of phosphate buffer solution, Tris-hydrochloric acid buffer solution, and sodium bicarbonate solution, and the concentration of the alkaline solution is 0.1-0.5 M.
[0022] In one embodiment of the present invention, in step (3), in the coating finishing solution, the volume fraction of the polyacrylate sizing agent is 15-30%, and the volume fraction of the kerosene thickener is 2-3%.
[0023] In one embodiment of the present invention, in step (3), the aerogel light-shielding coated fabric weighs 20-30 g / m more than the light-shielding fabric 2 .
[0024] In one embodiment of the present invention, in step (3), the temperature during drying is 150-180 °C, and the drying condition is 2-5 min.
[0025] In one embodiment of the present invention, in step (3), the preparation method of the light-shielding fabric includes the following steps:
[0026] ① Prepare the black slurry for foaming coating: Weigh nano-titanium dioxide particles, carbon black, polyacrylate sizing agent, ammonium stearate emulsion, and water, mix them evenly to obtain a mixed black slurry, and adjust the pH of the mixed slurry to 8-9 to obtain the black slurry for foaming coating;
[0027] ② Prepare the white slurry for foaming coating: Weigh polyacrylate sizing agent, titanium dioxide slurry, ammonium stearate emulsion, and water, mix them evenly to obtain a mixed white slurry, and adjust the pH of the mixed slurry to 8-9 to obtain the white slurry for foaming coating;
[0028] ③ Preparation of the light-shielding fabric: Use a foaming device to foam the slurries obtained in steps (1) and (2) respectively, and coat them on the fabric surface in the order of white slurry, black slurry, and white slurry. After each coating, bake at 150 - 180 °C for 2 - 5 minutes to obtain the light-shielding fabric.
[0029] In an embodiment of the present invention, in step (1), in the mixed black slurry, the mass fraction of the polyacrylate slurry is 70% - 85%, the mass fraction of the ammonium stearate emulsion is 2% - 10%, the mass fraction of the nano-titanium dioxide particles is 0.5% - 1%, the mass fraction of the carbon black is 0.1% - 0.5%, and the rest is water.
[0030] In an embodiment of the present invention, in step (2), in the mixed white slurry, the mass fraction of the polyacrylate slurry is 70% - 85%, the mass fraction of the titanium dioxide slurry is 10% - 15%, the mass fraction of the ammonium stearate emulsion is 2% - 10%, and the rest is water.
[0031] In an embodiment of the present invention, in step (3), the foaming ratio of the slurry is 1:3 - 1:4. After each coating and baking, the weight gain range of the fabric is 20 - 40 g / m 2 .
[0032] The present invention also provides a flame-retardant, heat-insulating, and light-shielding coating fabric prepared by the above method.
[0033] The present invention also provides an application of the above flame-retardant, heat-insulating, and light-shielding coating fabric in the fields of flame-retardant fabrics and sunshades.
[0034] Advantages of the present invention:
[0035] (1) In the present invention, first, a condensing agent and a condensation activator are used to condense nucleotides and DOPA together by using the amino group in nucleotides and the carboxyl group in DOPA (DOPA) to form a condensation product; the catechol structure in the DOPA part of the condensation product enables the condensation product to have a strong self-polymerization adhesion effect. After mixing with SiO2 aerogel particles, the condensation product self-adheres to the SiO2 aerogel particles to obtain modified aerogel particles. Since nucleotides contain phosphorus and nitrogen elements, and DOPA contains nitrogen elements, the condensation product of the two also has good flame-retardant properties. Therefore, modifying SiO2 aerogel particles with the condensation product can enhance the flame-retardant performance of SiO2 aerogel particles. Mixing the modified aerogel particles and polyacrylate emulsion and coating them on the surface of the light-shielding fabric can prepare a multi-functional fabric with flame retardancy, heat insulation, and light shielding.
[0036] (2) The preparation process of AMP-Na2-DOPA-SiO2 aerogel particles is mild, simple, and pollution-free. The modified aerogel particles have no adverse effects on human health and the environment. After accidents such as fires, no toxic gases will be produced when the flame retardant burns.
[0037] (3) In the present invention, the condensation product has strong self-polymerization adhesion properties and can firmly adhere to the nano-SiO2 aerogel particles. Moreover, the modified aerogel particles are dispersed in the coating film, enabling the modified aerogel particles to be firmly combined in the coating, endowing the sunshade fabric with a durable and stable finishing effect.
[0038] (4) The flame-retardant and heat-insulating aerogel light-shielding coating fabric prepared by the method of the present invention has excellent flame retardancy and heat insulation properties. The afterflame time and smoldering time of the fabric are both less than 2 s, and the damaged length is less than 6 cm. The heat insulation temperature difference value of the fabric is relatively large, greater than 15.5 °C.
[0039] (5) The flame-retardant and heat-insulating aerogel light-shielding coating fabric prepared by the method of the present invention also has excellent washability. Before and after washing, the flame retardancy of the fabric shows no obvious decline, and the heat insulation temperature difference value (ΔT) of the specimen in the heat insulation test is relatively large before and after washing, indicating that the sunshade fabric prepared by the method described in the present invention has good heat insulation effect and the finishing effect has washability. Specific Embodiments
[0040] The following are the preferred embodiments of the present invention. It should be understood that the embodiments are for better explaining the present invention and are not used to limit the present invention.
[0041] Testing Methods:
[0042] (1) Flame Retardancy: Refer to "GBT 5455-2014 Determination of the Damaged Length, Smoldering and Afterflame Time of Textiles in the Vertical Direction for Combustion Performance", and conduct tests according to Condition B in the standard to calculate the afterflame time, smoldering time and damaged length of the specimen.
[0043] (2) Heat Insulation Performance: Refer to "HG / T 4341-2012 Heat Reflective Coatings for Metal Surfaces", and use a self-made device to measure the heat insulation performance of the sunshade material; the device is divided into upper and lower parts, namely the irradiation chamber and the heat insulation chamber, which are horizontally separated by the sunshade material (the coated surface of the material faces upward); an infrared light source is suspended in the irradiation chamber, 20 cm away from the surface of the specimen; digital thermometers are respectively placed on the surface of the specimen and 5 cm vertically below the specimen in the heat insulation chamber, and the temperature difference between the two test positions is recorded, denoted as the heat insulation temperature difference ΔT (°C).
[0044] Raw Materials Used in the Embodiment:
[0045] Polyester Fabric: Pure polyester shuttle-woven fabric, 95 g / m 2 ;
[0046] 5'-Adenylic acid disodium salt: purity 99%;
[0047] DOPA: purity 98%;
[0048] 1-(3-Dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride: purity 98%
[0049] N-Hydroxysuccinimide: purity 98%;
[0050] SiO2 aerogel particles: pore size 20 μm, hydrophilic type;
[0051] Stearic acid emulsion: purchased from Tongxiang Hongyuan Textile Auxiliary Factory, model DT-100830C, solid content 30%.
[0052] Example 1
[0053] A preparation method of a flame-retardant, heat-insulating and light-shielding coating fabric for aerogel, comprising the following steps:
[0054] (1) Preparation of the condensation product: Using 0.1M acetic acid and sodium acetate, prepare a buffer solution with a pH of 6. In the buffer solution with a pH of 6, add EDC, NHS, AMP-Na2 and DOPA, and then stir and react at 40 °C for 5 hours. The final concentrations of each component in the solution are EDC 5 g / L, NHS 6 g / L, AMP-Na2 10 g / L, and DOPA 10 g / L. After the reaction, freeze-dry to obtain the condensate AMP-Na2-DOPA;
[0055] (2) Preparation of the AMP-Na2-DOPA-SiO2 aerogel particle dispersion: Using 0.1M sodium dihydrogen phosphate and disodium hydrogen phosphate, prepare a buffer solution with a pH of 8. In the buffer solution with a pH of 8, add the AMP-Na2-DOPA prepared in step (1) to make its concentration in the solution 5 g / L, add nano-SiO2 aerogel particles to make its concentration in the solution 40 g / L, and then stir and react at room temperature for 3 hours. After the reaction, obtain the AMP-Na2-DOPA-SiO2 aerogel particle dispersion;
[0056] (3) Preparation of AMP-Na2-DOPA-SiO2 aerogel light-shielding coating fabric: Take the AMP-Na2-DOPA-SiO2 aerogel particle dispersion prepared in step (2), add polyacrylate sizing agent and kerosene thickener to it to prepare a coating finishing solution. The mass fraction of polyacrylate sizing agent in the coating finishing solution is 15%, and the mass fraction of kerosene thickener is 2%. After stirring and thickening, it is coated on the surface of the light-shielding fabric and baked at 150 °C for 5 min to obtain the AMP-Na2-DOPA-SiO2 aerogel light-shielding coating fabric. The aerogel light-shielding coating fabric has a weight gain of 20 g / m compared to the light-shielding fabric. 2 。
[0057] Among them, the preparation method of the light-shielding fabric used in step (3) includes the following steps:
[0058] ① Preparation of black slurry for foaming coating: Weigh nano-titanium dioxide particles, carbon black, polyacrylate sizing agent, ammonium stearate emulsion and water, and mix them evenly to obtain a mixed black slurry. In the mixed black slurry, the mass fraction of polyacrylate sizing agent is 70%, the mass fraction of ammonium stearate emulsion is 4%, the mass fraction of nano-titanium dioxide particles is 0.5%, and the mass fraction of carbon black is 0.1%; Add a small amount of ammonia water to the mixed black slurry and adjust the pH of the slurry to 8-9 to obtain the black slurry for foaming coating;
[0059] ② Preparation of white slurry for foaming coating: Weigh polyacrylate sizing agent, titanium dioxide slurry, ammonium stearate emulsion and water, and mix them evenly to obtain a mixed white slurry. In the mixed white slurry, the mass fraction of polyacrylate sizing agent is 80%, the mass fraction of titanium dioxide slurry is 12%, and the mass fraction of ammonium stearate emulsion is 5%; Add a small amount of ammonia water to the mixed white slurry and adjust the pH of the slurry to 8-9 to obtain the white slurry for foaming coating;
[0060] ③ Foam the slurry with a whisk (foaming ratio 1:3), and coat it on the surface of the polyester fabric in the order of white slurry, black slurry and white slurry. Bake at 180 °C for 2 minutes after each coating to obtain the light-shielding coating fabric, and control the weight gain of the fabric after baking after each coating to be 30 g / m 2 。
[0061] Example 2
[0062] A preparation method of a flame-retardant and heat-insulating aerogel light-shielding coating fabric, including the following steps:
[0063] (1) Preparation of the condensation product: A buffer solution with a pH of 5 was prepared using 0.1 M acetic acid and sodium acetate. In the buffer solution with a pH of 5, EDC, NHS, AMP-Na2, and DOPA were added. Then, under the condition of 35 °C, the mixture was stirred and reacted for 3 hours. The final concentrations of each component in the solution were 6 g / L for EDC, 3 g / L for NHS, 8 g / L for AMP-Na2, and 6 g / L for DOPA. After the reaction, the condensate AMP-Na2-DOPA was obtained by freeze-drying;
[0064] (2) Preparation of the AMP-Na2-DOPA-SiO2 aerogel particle dispersion: A buffer solution with a pH of 8 was prepared using 0.1 M sodium dihydrogen phosphate and disodium hydrogen phosphate. In the buffer solution with a pH of 8, the AMP-Na2-DOPA prepared in step (1) was added to make its concentration in the solution 8 g / L, and nano-SiO2 aerogel particles were added to make their concentration in the solution 30 g / L. Then, under the condition of room temperature, the mixture was stirred and reacted for 5 hours. After the reaction, the AMP-Na2-DOPA-SiO2 aerogel particle dispersion was obtained;
[0065] (3) Preparation of the AMP-Na2-DOPA-SiO2 aerogel light-shielding coating fabric: Take the AMP-Na2-DOPA-SiO2 aerogel particle dispersion prepared in step (2), add polyacrylate sizing agent and kerosene thickener to it to prepare a coating finishing solution. The mass fraction of polyacrylate sizing agent in the coating finishing solution is 25%, and the mass fraction of kerosene thickener is 3%. After stirring and thickening, it was coated on the surface of the light-shielding fabric and baked at 180 °C for 2 min to obtain the AMP-Na2-DOPA-SiO2 aerogel light-shielding coating fabric. The aerogel light-shielding coating fabric has a weight gain of 25 g / m compared to the light-shielding fabric 2 .
[0066] Among them, the preparation method of the light-shielding fabric used in step (3) includes the following steps:
[0067] ① Preparation of the black slurry for the foaming coating: Weigh nano-titanium dioxide particles, carbon black, polyacrylate sizing agent, ammonium stearate emulsion, and water, and mix them evenly to obtain a mixed black slurry. In the mixed black slurry, the mass fraction of polyacrylate sizing agent is 80%, the mass fraction of ammonium stearate emulsion is 6%, the mass fraction of nano-titanium dioxide particles is 0.8%, and the mass fraction of carbon black is 0.3%. A small amount of ammonia water was added dropwise to the mixed black slurry to adjust the pH of the slurry to 9 to obtain the black slurry for the foaming coating;
[0068] ② Prepare the white slurry for the foaming coating: Weigh polyacrylate slurry, titanium dioxide slurry, ammonium stearate emulsion and water, and mix them evenly to obtain a mixed white slurry. In the mixed white slurry, the mass fraction of polyacrylate slurry is 85%, the mass fraction of titanium dioxide slurry is 10%, and the mass fraction of ammonium stearate emulsion is 8%; Add a small amount of ammonia water to the mixed white slurry and adjust the pH of the slurry to 8.5 to obtain the white slurry for the foaming coating;
[0069] ③ Use a whisk to foam the slurry (foaming ratio 1:4), and coat it on the surface of the polyester fabric in the order of white slurry, black slurry and white slurry. After each coating, bake it at 150 °C for 5 minutes to obtain a light-shielding coated fabric, and control the weight gain of the fabric after baking after each coating to be 35 g / m 2 。
[0070] Comparative Example 1:
[0071] The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 does not include steps (1) and (2). In step (3), the preparation method of the light-shielding coated fabric is as follows: Weigh polyacrylate slurry and kerosene thickener to prepare a coating finishing solution. In the coating finishing solution, the mass fraction of polyacrylate slurry is 25%, and the mass fraction of kerosene thickener is 3%. After stirring and thickening, coat it on the surface of the light-shielding fabric and dry it to obtain a light-shielding coated fabric, and control the weight gain of the coated fabric after drying relative to the light-shielding fabric to be 20 g / m 2 。
[0072] Among them, the preparation method of the light-shielding fabric in Comparative Example 1 includes the following steps:
[0073] ① Prepare the black slurry for the foaming coating: Weigh nano-titanium dioxide particles, carbon black, polyacrylate slurry, ammonium stearate emulsion and water, and mix them evenly to obtain a mixed black slurry. In the mixed black slurry, the mass fraction of polyacrylate slurry is 75%, the mass fraction of ammonium stearate emulsion is 4%, the mass fraction of nano-titanium dioxide particles is 0.6%, and the mass fraction of carbon black is 0.3%; Add a small amount of ammonia water to the mixed black slurry and adjust the pH of the slurry to 9 to obtain the black slurry for the foaming coating;
[0074] ② Prepare the white slurry for the foaming coating: Weigh polyacrylate slurry, titanium dioxide slurry, ammonium stearate emulsion and water, and mix them evenly to obtain a mixed white slurry. In the mixed white slurry, the mass fraction of polyacrylate slurry is 80%, the mass fraction of titanium dioxide slurry is 15%, and the mass fraction of ammonium stearate emulsion is 6%; Add a small amount of ammonia water to the mixed white slurry and adjust the pH of the slurry to 9 to obtain the white slurry for the foaming coating;
[0075] ③ Use a whisk to foam the slurry (foaming ratio 1:3.5), and coat it on the surface of the polyester fabric in three layers in the order of white slurry, black slurry, and white slurry. Bake at 160 °C for 3 minutes after each coating to obtain a light-shielding coated fabric, and control the weight gain of the fabric after baking after each coating to be 40 g / m 2 。
[0076] Comparative Example 2: Omit AMP-Na2
[0077] The difference between Comparative Example 2 and Example 1 is that AMP-Na2 was not added in step (1).
[0078] Comparative Example 3: Omit DOPA
[0079] The difference between Comparative Example 3 and Example 1 is that DOPA was not added in step (1).
[0080] Comparative Example 4: Omit SiO2 aerogel particles
[0081] The difference between Comparative Example 4 and Example 1 is that nano-SiO2 aerogel particles were not added in step (2).
[0082] Comparative Example 5: Do not add EDC and NHS
[0083] The difference between Comparative Example 5 and Example 1 is that EDC and NHS were not added in step (1).
[0084] Comparative Example 6: Excessive amount of DOPA
[0085] The difference between Comparative Example 6 and Example 1 is that in step (1), the concentration of DOPA was 20 g / L.
[0086] Comparative Example 7: Insufficient amount of DOPA
[0087] The difference between Comparative Example 7 and Example 1 is that in step (1), the concentration of DOPA was 0.5 g / L.
[0088] Comparative Example 8: Excessive amount of AMP-Na2
[0089] The difference between Comparative Example 8 and Example 1 is that in step (1), the concentration of AMP-Na2 was 15 g / L.
[0090] Comparative Example 9: Insufficient amount of AMP-Na2
[0091] The difference between Comparative Example 8 and Example 1 is that in step (1), the concentration of AMP-Na2 was 0.6 g / L.
[0092] The flame retardant properties of the samples in Examples 1-2 and Comparative Examples 1-9 were measured, including afterflame time, smoldering time, and char length; heat insulation temperature difference (ΔT1); the samples in Examples 1-2 and Comparative Examples 1-9 were washed with 1 g / L of detergent LS at 60 °C for 1 hour, and after drying, the flame retardant properties and heat insulation temperature difference (ΔT2) of the samples were measured again, and the data are listed in Table 1.
[0093] Table 1 Flame Retardant Properties and Heat Insulation Properties of Different Light-Shielding Fabrics
[0094]
[0095]
[0096] As can be seen from Table 1:
[0097] ① The flame retardant light-shielding coated fabric samples prepared by the method of the present invention have good flame retardant properties. The afterflame time and smoldering time are both less than 2 s, the char length is less than 6 cm, and the flame retardant properties show no obvious decline after washing; the heat insulation temperature difference value (ΔT) of the samples in the heat insulation test before and after washing is relatively large, indicating that the sunshade fabric prepared by the method described in the present invention has good heat insulation effect and the finishing effect has water-wash resistance.
[0098] ② For the light-shielding coated fabric prepared by coating and finishing polyester fabric by conventional process (Comparative Example 1), the afterflame time (15.2 s), smoldering time (23.2 s), and char length (18.7 cm) are much greater than those of the flame retardant light-shielding fabric prepared by the method of the present invention, indicating that the polyester sunshade fabric prepared by conventional process has no flame retardant properties; the heat insulation temperature difference values of Comparative Example 1 are relatively low (<4 °C), indicating that the heat insulation performance of the sunshade fabric prepared by conventional process is not ideal.
[0099] ③ In Comparative Example 2, AMP-Na2 in Example 1 was omitted to obtain a DOPA-SiO2 aerogel-coated light-shielding fabric without AMP-Na2. It can be seen that the light-shielding coated fabric without AMP-Na2 has no flame retardant properties, but the heat insulation temperature difference value (ΔT) of the sample in the heat insulation test is relatively large, indicating that the addition of DOPA-SiO2 aerogel endows the light-shielding fabric with better heat insulation performance.
[0100] ④ In Comparative Example 3, DOPA in Example 1 was omitted to obtain an AMP-Na2-SiO2 aerogel-coated light-shielding fabric without DOPA. It can be seen that Comparative Example 3 showed good flame retardant properties and heat insulation properties before washing, but after washing, the combustion test values were close to those of the sunshade fabric prepared by conventional process, that is, the flame retardant properties disappeared after washing; the AMP-Na2-SiO2 aerogel-coated light-shielding fabric showed good heat insulation properties, indicating that SiO2 aerogel is the key component for improving the heat insulation performance of the sunshade fabric.
[0101] ⑤In Comparative Example 4, the SiO2 aerogel particles in Example 1 were omitted to obtain an AMP-Na2-DOPA coated sunshade fabric without SiO2 aerogel particles. It can be seen that the flame retardancy and heat insulation properties of the sunshade fabric lacking SiO2 aerogel particles are lower than those of Example 1, indicating that SiO2 aerogel particles can improve both the flame retardancy and heat insulation properties of the sunshade fabric.
[0102] ⑥In Comparative Example 5, EDC and NHS in Example 1 were omitted, and the others were kept the same as in Example 1, that is, an AMP-Na2 / DOPA / SiO2 aerogel coated sunshade fabric was obtained. The difference from Example 1 is that AMP-Na2 was not condensed with DOPA. It can be seen that compared with Example 1, the flame retardancy of Comparative Example 5 disappeared after washing, indicating that the condensation effect of EDC and NHS is the key for the firm binding of AMP-Na2 in the coating.
[0103] ⑦In Comparative Example 6, the concentration of DOPA in Example 1 was adjusted to 20 g / L, and the other conditions were kept the same as in Example 1 to obtain an AMP-Na2-DOPA-SiO2 aerogel coated sunshade fabric. Compared with Example 1, under the condition of excessive DOPA, the flame retardancy and heat insulation properties of the prepared sunshade fabric did not improve but decreased. This is because excessive DOPA will polymerize and agglomerate into large particles, which cannot be evenly dispersed in the coating, resulting in poor dispersion of the combined AMP-Na2 and SiO2 aerogel particles in the coating and deteriorating finishing effect.
[0104] ⑧In Comparative Example 7, the concentration of DOPA in Example 1 was adjusted to 0.5 g / L, and the other conditions were kept the same as in Example 1 to obtain an AMP-Na2-DOPA-SiO2 aerogel coated sunshade fabric. Compared with Example 1, under the condition of too little DOPA, the flame retardancy of Comparative Example 7 decreased significantly after washing, indicating that DOPA is the key for the firm binding of AMP-Na2 in the coating. When the amount of DOPA is small, a large amount of AMP-Na2 not firmly bound to the coating is eluted during washing, resulting in a decrease in the flame retardancy of the sunshade fabric after washing.
[0105] ⑨In Comparative Example 8, the concentration of AMP-Na2 in Example 1 was adjusted to 15 g / L, and the other conditions were kept the same as in Example 1 to obtain an AMP-Na2-DOPA-SiO2 aerogel coated sunshade fabric. Compared with Example 1, under the condition of excessive AMP-Na2, the flame retardancy and heat insulation properties of Comparative Example 8 before washing are comparable to those of Example 1, but the flame retardancy of Comparative Example 8 decreased after washing. This is because excessive AMP-Na2 affects the adhesion of DOPA to SiO2 aerogel particles, and AMP-Na2-DOPA is eluted together during washing, resulting in a decrease in the flame retardancy of such fabric.
[0106] ⑩ Comparative Example 9 adjusted the concentration of AMP-Na2 in Example 1 to 0.6 g / L, and kept other conditions the same as those in Example 1, to obtain the shading fabric with the AMP-Na2-DOPA-SiO2 aerogel coating. Compared with Example 1, under the condition of too little dosage of AMP-Na2, the flame retardancy of Comparative Example 9 before and after washing was worse than that of Example 1, indicating that with too little dosage of AMP-Na2, the shading fabric could not achieve good flame retardant effect.
[0107] Although the present invention has been disclosed above with the preferred embodiments, it is not intended to limit the present invention. Anyone who is familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention should be defined by the claims.
Claims
1. A preparation method of a flame-retardant, heat-insulating, aerogel light-shielding coating fabric, characterized in that, Specifically, it includes the following steps: (1) Preparation of the condensation product: Add a condensing agent, a condensation activator, a nucleotide and / or a nucleoside salt, and DOPA to an acidic solution to obtain a mixed solution. Stir and react the mixed solution at 30 - 40 °C for 1 - 6 hours. After the reaction, freeze-dry to obtain the condensation product; (2) Preparation of the modified aerogel particle dispersion: Add the condensation product obtained in step (1) to an alkaline solution, and add nano-SiO2 aerogel particles thereto to obtain a reaction mixture. Stir and react the reaction mixture at room temperature for 1 - 6 hours. After the reaction, obtain the modified aerogel particle dispersion; (3) Preparation of the aerogel light-shielding coating fabric: Add a polyacrylate sizing agent and a kerosene thickener to the modified aerogel particle dispersion obtained in step (2) to prepare a coating finishing solution, and coat the coating finishing solution on the surface of the light-shielding fabric. Bake at 150 - 180 °C for 2 - 5 min to obtain the aerogel light-shielding coating fabric; The nucleotide includes 5'-adenosine monophosphate, and the nucleoside salt includes 5'-adenosine monophosphate monosodium or 5'-adenosine monophosphate disodium..
2. The preparation method according to claim 1, wherein, In step (1), the concentration of the condensing agent in the mixed solution is 1 - 10 g / L, the concentration of the condensation activator is 1 - 10 g / L, the concentration of the nucleotide and / or the nucleoside salt is 1 - 10 g / L, the concentration of DOPA is 1 - 10 g / L, the condensing agent is 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC), and the condensation activator is N-hydroxysuccinimide (NHS).
3. The preparation method according to claim 1, characterized in that, In step (1), the pH of the acidic solution is 4 - 6, the acidic solution includes at least one of hydrochloric acid, sulfuric acid, citric acid, acetic acid, and sodium acetate, and the concentration of the acid in the acidic solution is 0.1 - 0.5 M.
4. The preparation method according to claim 1, characterized in that, In step (2), in the reaction mixture, the concentration of the condensation product is 1 - 10 g / L, and the concentration of the nano-SiO2 aerogel particles is 5 - 50 g / L.
5. The preparation method according to claim 1, characterized in that, In step (2), the pH of the alkaline solution is 7 - 9, the alkaline solution is at least one of a phosphate buffer solution, a Tris-hydrochloric acid buffer solution, and a sodium bicarbonate solution, and the concentration of the alkaline solution is 0.1 - 0.5 M.
6. The preparation method according to claim 1, characterized in that, In step (3), in the coating finishing liquid, the volume fraction of the polyacrylate sizing agent is 15-30%, the volume fraction of the kerosene thickener is 2-3%, and the aerogel light-shielding coated fabric is 20-30 g / m heavier than the light-shielding fabric 2 .
7. The preparation method according to any one of claims 1 to 6, characterized in that, In step (3), the preparation method of the light-shielding fabric includes the following steps: ① Prepare the black slurry for foaming coating: Weigh nano-titanium dioxide particles, carbon black, polyacrylate sizing agent, ammonium stearate emulsion, and water, mix them evenly to obtain a mixed black slurry, and adjust the pH of the mixed slurry to 8 - 9 to obtain the black slurry for foaming coating. In the mixed black slurry, the mass fraction of the polyacrylate sizing agent is 70% - 85%, the mass fraction of the ammonium stearate emulsion is 2% - 10%, the mass fraction of the nano-titanium dioxide particles is 0.5% - 1%, the mass fraction of the carbon black is 0.1% - 0.5%, and the rest is water; ②Prepare the white slurry for the foaming coating: Weigh polyacrylate slurry, titanium dioxide slurry, ammonium stearate emulsion and water, mix them evenly to obtain a mixed white slurry, adjust the pH of the mixed slurry to 8-9 to obtain the white slurry for the foaming coating. In the said mixed white slurry, the mass fraction of the polyacrylate slurry is 70%-85%, the mass fraction of the titanium dioxide slurry is 10%-15%, the mass fraction of the ammonium stearate emulsion is 2%-10%, and the rest is water; ③ Preparation of the light-shielding fabric: Use a foaming device to foam the slurries obtained in steps (1) and (2) respectively, and coat them on the fabric surface in the order of white slurry, black slurry, and white slurry. After each coating, bake at 150-180°C for 2-5 minutes to obtain the light-shielding fabric. The foaming ratio of the slurry is 1:3-1:
4. After each coating and baking, the weight gain of the fabric ranges from 20 to 40 g / m 2 .
8. A flame-retardant, heat-insulating and light-shielding coating fabric made of aerogel prepared by the method according to any one of claims 1 to 7.
9. Application of the flame-retardant, heat-insulating and light-shielding coating fabric made of aerogel according to claim 8 in the fields of flame-retardant fabrics and sunshades.
Citation Information
Patent Citations
Alkaloid phosphate flame retardant and preparation method thereof
CN109400957A
Flame-retardant material and phosphorus-containing flame retardant and application thereof
CN111808461A